2020
DOI: 10.3389/fphy.2020.598420
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Anti-Stokes Raman Scattering Microscopy and Its Applications

Abstract: Coherent anti-Stokes Raman scattering (CARS) microscopy can provide high resolution, high speed, high sensitivity, and non-invasive imaging of specific biomolecules without labeling. In this review, we first introduce the principle of CARS microscopy, and then discuss its configuration, including that of the laser source and the multiplex CARS system. Finally, we introduce the applications of CARS in biomedicine and materials, and its future prospects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 93 publications
(114 reference statements)
0
27
0
Order By: Relevance
“…In addition, several studies have shown that lipid metabolism in the brain of patients with AD is closely related to the formation of Aβ plaques [9,10]. Coherent anti-Stokes Raman scattering (CARS) microscopy is an emerging label-free vibrational imaging with chemical selection that has been widely applied in biology and medical research [11][12][13][14][15][16][17]. Because CARS can obtain spectral information while achieving unlabeled imaging, it is highly suitable for studying lipid metabolism and lipid distribution in the brain as well as for the identification of abnormal accumulation of Aβ in AD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have shown that lipid metabolism in the brain of patients with AD is closely related to the formation of Aβ plaques [9,10]. Coherent anti-Stokes Raman scattering (CARS) microscopy is an emerging label-free vibrational imaging with chemical selection that has been widely applied in biology and medical research [11][12][13][14][15][16][17]. Because CARS can obtain spectral information while achieving unlabeled imaging, it is highly suitable for studying lipid metabolism and lipid distribution in the brain as well as for the identification of abnormal accumulation of Aβ in AD.…”
Section: Introductionmentioning
confidence: 99%
“…Bocklitz et al conducted a comparative study of hyperspectral SRS and CARS of human tissues, finding that cluster distributions in SRS and CARS are based on different spectral features, such that the combination of CARS and SRS data does not improve structure characterisation [134]. For further reading, Li et al published a recent comprehensive review of CARS that illustrated the range of applications in cell imaging, tissue imaging, biomedicine and material science [146].…”
Section: Coherent Anti-stokes Raman Scatteringmentioning
confidence: 99%
“…In addition, the backscattered CARS signal is generally much weaker than forward-directed ones. As a result, NIVI is gradually becoming a successful microscopic technique that has been used in studies of animal tumor models and skin diseases [ 63 , 64 , 65 , 66 ]. In the future, the development of supercontinuum sources and epi-detection techniques may eventually lead to broader applicability of NIVI-based OCT to address in vivo biological studies and medical applications.…”
Section: Nonlinear Interferometric Vibrational Imaging and Its Applic...mentioning
confidence: 99%